Influence of Euphorbia hirta extract on the growth, photosynthesis and antioxidant defense system in maize under drought stress - Han, M.; Kasim, S.; Yang, Z.; Deng, X.; Saidi, N. B.; Uddin, M. K.; Shuib, E. M. (Pleiades Publishing, 2024)
Biostimulant is enriched in nutrients and antioxidants have been used to promote plant growth and resist abiotic stresses. This study was conducted to evaluate the effects of foliar application of Euphorbia hirta extract (EHE) on growth, physiological and biochemical characteristics of maize (Zea mays L.) under drought stress conditions. Plants were sprayed with three different concentrations of EHE at 1, 3 and 5 g/L. The results showed that drought causes negative effects on plant height, fresh and dry weight and soluble sugar. Application of EHE significantly increased fresh and dry weight (FW: 11.9 ~ 22.6%; DW: 15.2 ~17.9%), chlorophyll content (Chl a: 38.3 ~ 64.4%; Chl b: 63.3 ~ 113.3%), soluble sugar (40.7 ~ 42.9%), GSH (22.4 ~ 85.7%), and compared to CK treatment under drought conditions, while decreased the level of MDA. In addition, drought stress stimulated phenolic, flavonoid, proline, GSH, MDA and antioxidant enzyme (CAT, POD and SOD) activities. Interestingly, the positive effect of EHE application with high concentration (5 g/L) was more effective than those of SWE. Therefore, EHE can is considered as a natural and inexpensive biostimulant for foliar application strategy to protect plants from drought stress.